PV Emulator based on DC-DC buck converter and PI Controller - El Asri Yassine; El Fadil Hassan; Lassioui Abdellah; Hasni Anwar; El Ancary Marouane; Bentalhik Issam; Koundi Mohamed (EPJ Web of Conferences)
This paper discusses the development of a photovoltaic panel emulator, based on the PV equivalent circuit, DC-DC converter, and PI controller, tailored for educational and scientific research uses. The emulator addresses common challenges such as high investment costs and spatial limitations. Its configurability allows adaptation to specific research needs and variable climatic conditions, making it a valuable tool for detailed study of photovoltaic systems. By enabling precise control and simulation under diverse scenarios, the emulator aids in reducing experimental costs and space requirements, thereby promoting more efficient solar technology research and education.